Overcoming The Difficulties Of Learning The Arabic Language Through Behavioral Counseling For University Students - Akla Akla; Fadhil Hardiansyah (Ijaz Arabi Journal of Arabic Learning, 2023)
Behavioral Counseling for students is currently being implemented as an alternative solution to the problem of difficulties in learning Arabic. Students learning difficulties are caused by high anxiety due to poor learning management. The process of overcoming Arabic learning difficulties through participatory Behavioral Counseling is described implicitly in this study. The goal of this study is to examine (1) the process of overcoming difficulties in learning Arabic using Behavioral Counseling, (2) the level of academic anxiety and learning attitudes of students before and after the implementation of Behavioral Counseling, and (3) whether Behavioral Counseling implementation can improve students' Arabic language skills. This study was designed employing a Mixed Method Research approach. The questionnaire respondents were 250 students from IAIN Metro and UIN RIL (Raden Intan Lampung) Indonesia. According to the questionnaire distribution results, 46 students of UIN RIL and 45 students of IAIN Metro Indonesia required counseling. Data were gathered through observation, questionnaires, interviews, and tests. The research findings are that behavioral counseling was given to two groups of students who had difficulty learning Arabic. The first step in providing Behavioral Counseling to both groups of students with learning disabilities was conducting an assessment. The primary objective of this assessment was to discover what behaviors respondents engaged in when learning Arabic. The observed behavior was a unique behavior related to the respondent's problems. The assessment results revealed some poor learning behaviors, such as being too lazy to study, lacking enthusiasm, and being confused, anxious, and depressed about learning tasks that were not understood. Thus, students needed to be more motivated to learn Arabic because they perceived it to be difficult. The second research finding shows that in both groups of respondents, the level of academic anxiety is in the low range. Following Behavioral Counseling, there was a significant change in learning attitudes and academic anxiety—respondents whose learning attitude was poor due to various factors improved after receiving Behavioral Counseling. Similarly, academic anxiety, which was initially high, decreased after behavioral counseling. The study's findings reveal that respondents' Arabic ability improves after receiving Behavioral Counseling. Respondents at UIN RIL have an average value of 64.57, while respondents at IAIN Metro have an average value of 62.71.